The Influence of Problem-Based Learning Model and Prior Knowledge toward the Physics Procedural Aplication Ability - Rezkawati Saad; A. Gemmy Antama Mukramin; Dian Pramana Putra; Tri Hastiti Fiskawarni (Jurnal Pendidikan Fisika, 2019)
The research was a quasi experiment which aimed at examining : (1) whether there were differences of Physics procedural application abilities of the students who are taught by employing problem based approach and the students taught conventionally, (2) whether there were differences of Physics procedural application abilities between the group who was taught by using problem based learning model and the group taught conventionally for high initial knowledge group, (3) whether there were differences of Physics procedural application abilities between the group who was taught by using problem based learning model and the group taught conventionally for low initial knowledge group, (4) whether there were interactions between problem based learning model and initial knowledge toward Physics procedural application abilities. The experiment involved two groups which were given different treatments. The experiment unit was the tenth grade students majoring in Tehnika at BP21P Barombong in Makassar with the total of 60 students, consisted of the tenth Teknika A grade with 30 students as the experiment class and the tenth Tehnika B grade with 30 students as control class. The experiment class was taught by using problem based learning and control class was taught conventionally. The test of hypothesis was conducted by two way variants analysis by using Microsoft Excel and SPSS program version 22 for windows at the significant level of 5%. The results of the research reveal that (1) There were differences of Physics procedural application abilities between the students taught by using problem based model and the students taught conventionally, (2) there are differences of Physics procedural application abilities between the group taught by using problem based learning model and the group taught conventionally for high initial knowledge, (3) there were differences of Physics procedural application abilities between the group taught by using problem based learning model and the group taught conventionally for low initial knowledge, and (4) there was not interaction between problem based learning model and initial knowledge toward Physics procedural application abilities to the tenth grade students majoring in tehnika at BP21P Barombong in Makassar.Keywords: Physics Procedural Application Abilities, Physics Initial Knowledge, Problem Based LearningPenelitian eksprimen yang bertujuan untuk mengetahui:(1) ada tidaknya perbedaan kemampuan aplikasi prosedural fisika pada peserta didik yang diajar dengan pendekatan berbasis masalah dengan peserta didik yang diajarkan secara konvensional;(2) ada tidaknya perbedaan kemampuan aplikasi prosedural fisika antara kelompok yang diajar menggunakan model pembelajaran berbasis masalah dan yang diajar secara konvensional untuk kelompok pengetahuan awal tinggi; (3)ada tidaknya perbedaan kemampuan aplikasi prosedural fisika antara kelompok yang diajar menggunakan model pembelajaran berbasis masalah dan yang diajar secara konvensional kelompok pengetahuan awal rendah;(4)ada tidaknya interaksi antara model pembelajaran berbasis masalah masalah dan  pengetahuan awal terhadap kemampuan aplikasi prosedural fisika. Eksprimen ini melibatkan dua kelompok yang diberi perlakuan yang berbeda . Satuan eksprimennya adalah peserta didik kelas X tehnika di BP2IP Barombong Makassar sebanyak 60 orang, kelas X tehnika A sebanyak 30 orang sebagai kelas eksprimen dan kelas tehnika B  sebanyak 30 orang sebagai kelas kontrol. Kelas eksprimen diajar  secara pembelajaran berbasis masalah dan kelas kontrol diajar secara konvensional. Pengujian hipotesis dilakukan dengan menggunakan analisis varians dua arah dengan menggunakan program Microsoft Excel dan SPSS versi 22 for windows dengan taraf signifikansi 5 % hasil penelitian menunjukkan bahwa(1) Terdapat perbedaan kemampuan aplikasi prosedural fisika antara kelompok yang diajar menggunakan model berbasis masalah dan peserta didik yang diajar secara konvensional (2)Terdapat perbedaan kemampuan aplikasi prosedural fisika antara kelompok yang diajar menggunakan model pembelajaran berbasis masalah dan yang diajar secara konvensional untuk Pengetahuan awal tinggi (3)Terdapat perbedaan kemampuan aplikasi prosedural fisika antara kelompok yang diajar menggunakan model berbasis masalah dan peserta didik yang diajar secara konvensional untuk pengetahuan awal rendah (4)Tidak terdapat interaksi antara model pembelajaran berbasis masalah Pengetahuan awal terhadap kemampuan aplikasi prosedural fisika pada peserta didik kelas X tehnika BP2IP Barombong Makassar.Kata kunci: Kemampuan aplikasi prosedural fisika, Pengetahuan awal fisika, berbasis masalah